Hifz Alaql: promoting social research skills among IIUM undergraduate students - Eid, Iyad Muhammad; Rokis, Rohaiza; Syed Hussien, Sh Fatimah Alzahrah; Sulaiman, Szariannie (Academia Industry Networks, 2020)
This paper discusses the outcomes of a recent research training programme targeting undergraduate students. The programme was conducted at the Department of Sociology and Anthropology by selected academics through two objectives; the preservation of intellect, one of the five dimensions of Maqasid al-Shari’ah, as well as the fourth goal of the Sustainable Development Goals (SDGs) which emphasizes on acquiring the knowledge and skills needed to promote sustainable development. The paper focuses on the research- based learning experience of about 700 undergraduate students studying at different departments at the International Islamic University Malaysia. The students were required to go to fieldwork and conduct mini social research projects about certain social issues by employing qualitative research approach. Working on the basis of teams, the students created remarkable research projects presented in the form of written reports, oral presentations and open discussions. Besides, the programme enhanced their communication and presentation skills. It also successfully managed to produce the first social research collection book titled “Khalduniyyat”. The book documented accomplished research projects showing that undergraduate students, under good guidance, can be involved in social research projects and generate knowledge.